Reactogenicity among health care workers following a BNT162b2 or mRNA-1273 second dose after priming with a ChAdOx1 nCOV-19 vaccine. (June 2022) - Baldolli, Aurelie; Fournier, Anna; Verdon, Renaud; Michon, Jocelyn
Abstract: Objectives: In March 2021, French authorities recommended a heterologous second dose of the mRNA vaccine for persons aged <55 years, with administration 9 to 12 weeks after the first dose of ChAdOx1 nCoV-19. This recommendation was despite a lack of data on the reactogenicity and safety of the regimen. Since then, several studies have shown an acceptable short-term safety profile of ChAdOx1 nCoV-19 and BNT162b2 heterologous vaccination, although some transient increased reactogenicity has been described. Methods: We performed a single-centre prospective observational cohort study among health care workers (HCWs) at a tertiary care hospital to assess the reactogenicity of the BNT162b2 and mRNA-1273 vaccines administered as a second dose in participants primed with ChAdOx1 nCoV-19. Results: Among 1184 HCWs, 356 (30%) agreed to participate. Of the participants, 32.3% were male, and the mean age was 35 years (standard deviation: 10.1 years). Of the participants, 229 received BNT162b2 and 127 received mRNA-1273. A systemic reaction was observed in 130 of 229 (56.8%) and 100 of 127 (78.7%) HCWs, respectively. Injection site reactions were generally limited (grade 1 or 2 in 163 of 229 (97.6%) and 90 of 127 (85.7 %) HCWs, respectively). After adjustment for age, sex, and HCW role, receiving the mRNA-1273 vaccine was associated with higher reactogenicity with more grade 3 side effects (adjusted OR (aOR): 3.34; 95% CI, 1.91–5.85), more systemic symptoms (aOR: 2.82; 95% CI, 1.69–4.7), and not being able to work (aOR: 8.35; 95% CI, 3.78–18.44) compared with receiving the BNT162b2 vaccine. Discussion: Among patients receiving the mRNA1273 vaccine as a second dose, our study confirms good tolerance of the heterologous schedule with a higher risk of short-term side effects in comparison with patients receiving the BNT162b2 vaccine.